Pengaruh Literasi Keuangan, Kontrol Diri dan Perilaku FoMO terhadap Perilaku Pengelolaan Keuangan (Studi Kasus Mahasiswa Prodi Akuntansi FE Undiksha): Studi Kasus Mahasiswa Prodi Akuntansi FE Undiksha - Gst Ag Ayu Pt Ratna Widiantari; Gst. Ayu Ketut Rencana Sari Dewi,S.E.,M.Si (Universitas Pendidikan Ganesha, 2024)
The aim of this research is to determine the influence of Financial Literacy, Self-Control and FoMO Behavior on Financial Management Behavior (Case Study of Undiksha FE Accounting Study Program Students). This research design is quantitative research. The type of data used in this research is quantitative data. The data sources in this research are secondary data and primary data. The population used in the research were active students of the 2019-2021 Bachelor of Accounting study program. The sample determination method uses Proportionate Stratified Random Sampling. The number of samples in this study was 261 active students of the 2019-2021 Bachelor of Accounting study program. The test results state that the Financial Literacy variable has a positive and significant effect on Financial Management Behavior, the Self-Control variable has a positive and significant effect on Financial Management Behavior and the FoMO variable has a negative and significant effect on Financial Management Behavior